2020
DOI: 10.1021/acschemneuro.0c00448
|View full text |Cite
|
Sign up to set email alerts
|

Further Studies on Triazinoindoles as Potential Novel Multitarget-Directed Anti-Alzheimer’s Agents

Abstract: The inadequate clinical efficacy of the present anti-Alzheimer’s disease (AD) drugs and their low impact on the progression of Alzheimer’s disease in patients have revised the research focus from single targets to multitarget-directed ligands. A novel series of substituted triazinoindole derivatives were obtained by introducing various substituents on the indole ring for the development of multitarget-directed ligands as anti-AD agents. The experimental data indicated that some of these compounds exhibited sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 61 publications
0
20
0
Order By: Relevance
“…It was prepared to ensure structural correctness for hydrogen consistency, bond orders, steric clashes and charges using protein preparation wizard of Maestro. The prepared structure was then used for the generation of grid [42] . The receptor grid was generated using receptor grid generation tool of Maestro by considering the centroid of co‐crystallized ligand HXA (docosahexaenoic acid).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was prepared to ensure structural correctness for hydrogen consistency, bond orders, steric clashes and charges using protein preparation wizard of Maestro. The prepared structure was then used for the generation of grid [42] . The receptor grid was generated using receptor grid generation tool of Maestro by considering the centroid of co‐crystallized ligand HXA (docosahexaenoic acid).…”
Section: Methodsmentioning
confidence: 99%
“…The molecular docking of nine designed conjugates against HBFABP was performed using extra precision (XP) algorithm of Glide docking module of Maestro. The OPLS3e force field was used in simulations [42] . The conjugates were then ranked based on their docking scores.…”
Section: Methodsmentioning
confidence: 99%
“…Today, millions of people are afflicted with this disease, and the number is projected to increase in the next few years ( Sang et al, 2018 ). Different factors such as inflammation, reduced acetylcholine (ACh) concentration, β-amyloid (Aβ) plaque formation, τ-protein aggregation, and oxidative stress cause AD, while the main reason is not perfectly understood ( Patel et al, 2020 ). One of the most significant factors is the declined cholinergic activity resulting from ACh degradation by acetylcholinesterase (AChE), which affects memory loss.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most significant factors is the declined cholinergic activity resulting from ACh degradation by acetylcholinesterase (AChE), which affects memory loss. Conventionally approved drugs are mostly AChE inhibitors, increasing the amount of ACh in the synapses and decelerating the advancement of AD ( Reddy et al, 2017 ; Li et al, 2018 ; Patel et al, 2020 ). Moreover, studies on the structure of AChE have indicated that it has two main sites for binding, including a peripheral anionic site (PAS) and a catalytic anionic site (CAS).…”
Section: Introductionmentioning
confidence: 99%
“…Among heterocyclic compounds, indoles have been investigated extensively due to their interesting versatility [ 23 ] . Many natural and synthetic derivatives of indoles have indeed shown a wide spectrum of pharmacological properties including antibacterial [ 24 - 27 ] , antifungal [ 28 , 29 ] , anti-inflammatory [ 30 ] , antihistamine [ 31 ] , anticholinesterase, antioxidant [ 32 ] , anti-diabetic [ 33 ] , antiviral [ 34 ] and anticancer activities [ 35 , 36 ] .…”
Section: Introductionmentioning
confidence: 99%